The Role of Islamic Educational Curriculum in Shaping the Character of Muslim Generations - Hasibuan, Kalayo; Fadly, Khairul; Waruwu, Wahyu Suhendra (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic education has long played a vital role in shaping the ethical and moral development of Muslim youth. It is not merely an academic pursuit but an essential process for cultivating a well-rounded, pious, and ethical generation. In light of the challenges presented by modern technology, globalization, and the industrial revolution, the role of Islamic education becomes increasingly complex. This paper explores how the Islamic educational curriculum contributes to the formation of character among Muslim youth. By examining key educational settings such as Islamic boarding schools, family education, and modern Islamic educational institutions, the paper highlights the pivotal role of Islamic values in fostering responsible, empathetic, and morally grounded individuals. The study draws upon various scholarly perspectives to explore the current state of Islamic education and its potential to adapt to modern challenges.